Nontyphi Salmonella Empyema with Bronchopleural Fistula in a Patient with Human Immunodeficiency Virus - Douglas Bretzing; Tasnim Lat; Andrew Shakespeare; Mary Lee; Salim Surani; Shekhar Ghamande (Case Reports in Pulmonology)
Patients with human immunodeficiency virus (HIV) have an increased risk of inoculation with nontyphoid Salmonella compared to the general population. While nontyphoid Salmonella commonly manifests as gastroenteritis, Salmonella bacteremia can be seen in patients with HIV. We present a case of disseminated Salmonellosis in a patient with HIV complicated by bronchopleural fistula and secondary empyema. Case Presentation. A 40-year-old African American male with HIV noncompliant with HAART therapy presented with complaints of generalized weakness, weight loss, cough, night sweats, and nonbloody, watery diarrhea of four weeks’ duration. A computed tomography (CT) scan demonstrated a bilobed large, thick-walled cavitary lesion in the right upper lobe communicating with the pleural space to form a bronchopleural fistula. Thoracentesis yielded growth of nontyphi Salmonella species consistent with empyema; he was treated with intravenous Ceftriaxone and underwent placement of chest tube for drainage of empyema with instillation of alteplase/dornase twice daily for three days. Repeat CT chest showed a hydropneumothorax. The patient subsequently underwent video-assisted thoracoscopy with decortication. The patient continued to improve and follow-up CT chest demonstrated improved loculated right pneumothorax with resolution of the right bronchopleural fistula and resolution of the cavitary lesions. Discussion. We describe one of the few cases of development of bronchopulmonary fistula and the formation of empyema in the setting of disseminated Salmonella. Empyema complicated by bronchopulmonary fistula likely led to failure of intrapleural fibrinolytic therapy and the patient ultimately required decortication in addition to antibiotics. While Salmonella bacteremia can be seen in immunocompromised patients, extraintestinal manifestations of Salmonella infection such as empyema and bronchopleural fistulas are uncommon. Bronchopleural fistulas most commonly occur as a postoperative complication of pulmonary resection. Conclusions. This case highlights the unusual pulmonary manifestations that can occur due to disseminated Salmonella in an immunocompromised patient as well as complex management decisions related to these complications.